Validitas Modul Berbasis Kearifan Lokal Kabupaten Tuban Bagi Siswa Kelas IV Sekolah Dasar - Arik Umi Pujiastuti (JURNAL PENDIDIKAN DASAR NUSANTARA, 2021)
Abstract: The module is one of the lessons students can use on their own. Having thematic learning done in sd makes learning focused on subjects that are close to student or contextual life. One of the themes was where I lived. The theme has not yet been obtained with local wisdom from tuban. The problem made researchers an alternative breakthrough by developing the local magic-based module of tuban district. The purpose of research is to describe the validity of the developed module, which is a local prudence based module. Validity of the module is viewed at the worthiness level of the module based on validation performed by design experts, materials experts, and linguists, thus the instrument used is a validation sheet. The measure of worthiness is demonstrated by the percentage of the validator assessment of design experts, materials experts and linguists. Based on the results of 92% % designs with the highest criteria, from a materials assessment of 75% with viable criteria, and a linguist assessment of 85% with the most viable criteria. Validation results from all three experts indicate an 84% increase in the module’s adjust-level efficiency with very reasonable criteria Keywords: Key Words: Validity of the module, based on local prudence of the tuban district